The Roles of α2-Antiplasmin and Plasminogen Activator Inhibitor 1 (PAI-1) in the Inhibition of Clot Lysis - Robbie, Linda A; Booth, Nuala A; Croll, Alison M; Bennett, Bruce (Thrombosis and Haemostasis, 1993)
The relative importance of the two major inhibitors of fibrinolysis, α2-antiplasmin (α2-AP) and plasminogen activator inhibitor (PAI-1), were investigated using a simple microtitre plate system to study fibrin clot lysis in vitro. Cross-linked fibrin clots contained plasminogen and tissue plasminogen activator (t-PA) at concentrations close to physiological. Purified α2-AP and PAI-1 caused dose-dependent inhibition. All the inhibition due to normal plasma, either platelet-rich or poor, was neutralised only by antibodies to α2-AP. Isolated platelets, at a final concentration similar to that in blood, 2.5 × 108/ml, markedly inhibited clot lysis. This inhibition was neutralised only by antibodies to PAI-1. At the normal circulating ratio of plasma to platelets, α2-AP was the dominant inhibitor. When the platelet:plasma ratio was raised some 20-fold, platelet PAI-1 provided a significant contribution. High local concentrations of PAI-1 do occur in thrombi in vivo, indicating a role for PAI-1, complementary to that of α2-AP, in such situations.